IDENTITAS DAN MOBILITAS SOSIAL PRIYAYI DALAM NOVEL PARA PRIYAYI KARYA UMAR KAYAM - Fanani, Ahwan (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Novel with Javanese cultural setting is a phenomenon in Indonesian literary work. Umar Kayam in Para Priyayi provides vivid picture of the life of a specific Javanese aristocrat called priyayi from last period of Colonial to Independence Era. This article seeks to reveal identity and social mobility of priyayi, using sociology of literature approach. The article shows that Sastrodarsono, main character in the novel, is able to mobilize upward socially and attach to priyayi class as well as to its value, commitment and in-group feeling. Sosrodarsono who came from lower class in Javanese society was able to reach aristocrat status (priyayi) and built his own aristocrat dynasty. He internalizes priyayis’ values and resocializes it to his family. The novel gives brief spectacle on social mobilization of Javanese aristocrat family and elements shaping the identity of priyayi. Kayam succesfully revives the priyayi life in his work so that his fiction contains cultural explanation just like anthropological works do.